Geographical information system (GIS) in Malaysian planning education - Ibrahim, Mansor; Abdullah, Muhammad Faris; Abdul Samad, Dazilah (2004)
In most developed countries, the major users of GIS are not restricted to planning authorities at local, regional, and central government agencies, but covered across other non-planning agencies like engineering firms, resource management firms, and increasingly, financial, real estate and marketing firms. In Malaysia, it is not an exception though the coverage is still not wide spread and some of them are in infant stages. Particularly in urban and regional planning, GIS is being used in all the development plan preparation but it is not being fully exploited. In many instances, this is being limited to mapping only, as if GIS software is just graphic software where its use is solely for the purpose of maps and plans production. It is not surprising as most of the planners are not well-versed in GIS and they are not properly trained in their planning education either locally or overseas. This paper specifically looks at GIS training in local planning schools. Content analysis of the syllabus, extent of GIS application and its importance, and issues pertaining to GIS education are discussed.